A new key-site for the end of Lower Palaeolithic and the onset of Middle Palaeolithic at Etricourt-Manancourt (Somme, France). (21st July 2016) - Hérisson, David; Coutard, Sylvie; Goval, Emilie; Locht, Jean-Luc; Antoine, Pierre; Chantreau, Yoann; Debenham, Nick
Abstract: New Palaeolithic sites are rare for MIS 11 to 9 in Eurasia. The discovery and the excavation of a large new site in 2012 at Etricourt-Manancourt (Somme, France) is an exceptional event. In 2010, a Palaeolithic evaluation was undertaken at a future retention basin by Emilie Goval on 170, 000 square metres. The evaluation produced many flint artefacts, demonstrating the existence of at least two important Middle Palaeolithic sites. In 2012, an excavation on one of the sites was conducted by David Hérisson over 6 months and covering 4500 square metres. This excavation was undertaken by a multidisciplinary scientific team, including prehistorians and geomorphologists. This allows us to apply a reliable chronostratigraphic approach based on the analysis of the Glacial-interglacial successions. Five in situ Palaeolithic occupations have been excavated, dating from 330 to 70 ka. The youngest occupation dates from 70 to 80 ka (Weichselian) and corresponds to a recent phase of the Middle Palaeolithic. The next two layers belong to the Early Middle Palaeolithic, between 190 and 240 ka (Saalian). Finally, the two oldest layers have dates between 330 and 280 ka (Saalian) and belong to the Lower Palaeolithic. In addition to the archaeology, the sedimentary sequence is very thick (11 m high) and presents for the first time in Northern France a detailed record of the three last interglacial–glacial cycles. This paper presents the first archaeological and chronostratigraphic results of the excavation of Etricourt-Manancourt and its input with high resolution data to discuss behavioural changes occurring at the end of the Lower Palaeolithic and the onset of the Middle Palaeolithic.